IMPLEMENTASI MODUL ARIS (ANXIETY AND DEPRESSION REDUCTION THROUGH ISLAMIC SPIRITUAL CARE) DALAM MEMENUHI KEBUTUHAN SPIRITUAL PASIEN - Citra Wisuda, Aris; Suraya, Citra; Emiliasari, Dian (Institut Citra Internasional, 2024)
Spirituality is a fundamental need for every individual. Patients undergoing treatment, especially those with chronic, critical, or terminal conditions, often experience anxiety related to pain, uncertainty, and death. For patients in such conditions, spirituality becomes a primary source of calm and healing power. The ARIS (Anxiety and Depression Reduction Through Islamic Spiritual Care) module was developed as a guide to meet patients' spiritual needs through a structured Islamic approach. This study aims to explore the implementation of spiritual nursing care using the ARIS module, particularly for patients experiencing anxiety and depression. The method used follows the Kirkpatrick Model, including theoretical explanations, detailed concepts of spiritual care, and role-play sessions. This activity will be conducted over four weeks with patients experiencing chronic illness at Siti Khadijah Islamic Hospital in Palembang in 2024, through dissemination sessions and direct practice. Analysis results show that the ARIS module effectively meets patients' spiritual needs, thereby reducing their anxiety and depression. This module includes a prayer guide, healing prayers, and Al-Quran murottal, which are regarded as complete and practical by both nurses and patients. The ARIS module is recommended as a means of spiritual care to support comprehensive and holistic professional nursing care